2016
DOI: 10.5507/bp.2016.044
|View full text |Cite
|
Sign up to set email alerts
|

The long-term effects of probiotics in the therapy of ulcerative colitis: A clinical study

Abstract: Aim.Intestinal dysbiosis seems to be the leading cause of inflammatory bowel diseases, and probiotics seems to represent the proper support against their occurrence. Actually, probiotic blends and anti-inflammatory drugs represent a weapon against inflammatory bowel diseases. The present study evaluates the long-term (2 years) effects of combination therapy (mesalazine plus a probiotic blend of Lactobacillus salivarius, Lactobacillus acidophilus and Bifidobacterium bifidus strain BGN4) on ulcerative colitis ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 34 publications
0
46
0
3
Order By: Relevance
“…Treatment with probiotics together with commonly used anti-inflammatory drugs seems to be a more effective solution in comparison to treatment with probiotics alone. Palumbo and co-workers [ 95 ] demonstrated the positive effect of mesalazine use (Mesavancol ® 1200 mg CPR, Giuliani spa, Milan, Italy) with the probiotic mix ( Lactobacillus salivarius, Lactobacillus acidophilus, and Bifidobacterium bifidum strain BGN4; Acronelle ® , Bromatech SRL, Milan, Italy) among UC patients. The group with the double treatment showed reduced recovery time, weaker activity of the disease, and they presented a better endoscopic picture.…”
Section: Probiotics Treatment and Protection From Ibdmentioning
confidence: 99%
“…Treatment with probiotics together with commonly used anti-inflammatory drugs seems to be a more effective solution in comparison to treatment with probiotics alone. Palumbo and co-workers [ 95 ] demonstrated the positive effect of mesalazine use (Mesavancol ® 1200 mg CPR, Giuliani spa, Milan, Italy) with the probiotic mix ( Lactobacillus salivarius, Lactobacillus acidophilus, and Bifidobacterium bifidum strain BGN4; Acronelle ® , Bromatech SRL, Milan, Italy) among UC patients. The group with the double treatment showed reduced recovery time, weaker activity of the disease, and they presented a better endoscopic picture.…”
Section: Probiotics Treatment and Protection From Ibdmentioning
confidence: 99%
“…Thus, probiotics have been proposed to alter the gut microbiota with the goal of decreasing stimulation of the intestinal immune system, preventing epithelial dysfunction, and reducing permeability of the gut mucosa. A long-term UC study comparing daily oral mesalazine 1200 mg monotherapy to daily oral mesalazine 1200 mg in combination with bidaily probiotics (blend of Lactobacillus salivarius , Lactobacillus acidophilus , and Bifidobacterium bifidus strain BGN4) found significant disease improvement based on the Modified Mayo Disease Activity Index (MMDAI) after 18 months of treatment with combination therapy compared to monotherapy [ 85 ]. Other studies found that probiotics, specifically VSL#3, were as effective as mesalazine in preventing UC relapse and were an effective treatment for pouchitis [ 86 , 87 ].…”
Section: Multidisciplinary Carementioning
confidence: 99%
“…In particular, Bifidobacterium bifidum BGN 4 seems to reduce the production of pro-inflammatory cytokines, thanks to the chiro-inositol present in its cell membrane [ 154 ]. According to a recent study [ 155 ], the administration of a specific probiotic blend containing Bifidobacterium bifidum BGN 4, Lactobacillus salivarius and Lactobacillus acidophilus (Acronelle ® , Bromatech srl, Milan, Italy) decreases inflammation in patients with IBD, in combination with mesalazine treatment.…”
Section: Implications Of the New Hypothesismentioning
confidence: 99%